PEMANFAATAN MEDIA SOSIAL INSTAGRAM SEBAGAI MEDIA INFORMASI PADA AKUN @MEDANTALK - Syavina Nadhira Lubis; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research is titled "Utilizing Instagram Social Media as Information Media on the @medantalk Account." The aim is to understand how the Instagram account @medantalk utilizes Instagram social media as an information platform. The research employs a qualitative approach, specifically qualitative descriptive methodology. Data is collected through participant observation, where the author actively participates in the research to obtain accurate observational results. The theoretical framework utilized is Pierre Levy's New Media Theory. The findings indicate that the use of Instagram as an information medium on the @medantalk account offers an effective and efficient way of conveying information, as it is easily accessible and consistently updated. Followers of the @medantalk Instagram account also utilize it as a means to obtain accurate and timely information about the city of Medan.